2013
DOI: 10.1186/1471-2458-13-103
|View full text |Cite
|
Sign up to set email alerts
|

Trends and risk factors of hyperglycemia and diabetes among Kuwaiti adults: National Nutrition Surveillance Data from 2002 to 2009

Abstract: BackgroundCurrent prevalence estimates for diabetes in Arabian Gulf countries are some of the world’s highest, yet regional trends and contributing factors are poorly documented. The present study was designed to determine temporal changes in the prevalence of impaired fasting glucose (IFG) and diabetes and associated factors in Kuwaiti adults.MethodsData analysis from the nationally representative cross-sectional Kuwait National Nutrition Surveillance System. 2745 males and 3611 females, aged 20–69 years, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
5
18
0
Order By: Relevance
“…According to our findings, increasing age was an important risk factor associated with DM in Bisha province, which is in agreement with other reports from other parts of Saudi Arabia (Al Hayek et al, 2014;Amin et al, 2014;Murad et al, 2014) and neighboring countries (Ahmed et al, 2013;Ali, Mehrass, Al-Adhroey, Al-Shammakh & Amran, 2016). Ammarasinghe et al (2015) proposed that geriatric changes in the body systems might invariably contribute to this association.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to our findings, increasing age was an important risk factor associated with DM in Bisha province, which is in agreement with other reports from other parts of Saudi Arabia (Al Hayek et al, 2014;Amin et al, 2014;Murad et al, 2014) and neighboring countries (Ahmed et al, 2013;Ali, Mehrass, Al-Adhroey, Al-Shammakh & Amran, 2016). Ammarasinghe et al (2015) proposed that geriatric changes in the body systems might invariably contribute to this association.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, Al-Nozha et al (2004) found that males were overall having higher prevalence of DM than females in Riyadh capital, Saudi Arabia. Similar findings have been reported in the neighboring countries, such as in Sultanate Oman (El-Shafie & Rizvi, 2010) and in Kuwait (Ahmed, Waslien, Al-Sumaie, Prakash & Allafi, 2013). In addition, the association between diabetes and gender has been the focus of several studies with varying reports.…”
Section: Discussionsupporting
confidence: 68%
“…However, in Kuwait, the official criterion used for diagnosing and classifying diabetes mellitus is the WHO criterion,23 and so that was used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Second, students emerging from these health professional programmes need to support the overall health of their patients and their communities; one way is to serve as credible role models for health promotion (12,13). This is especially true in the current health climate where NCDs that are largely lifestyle related are the leading causes of premature death and disability in the Middle East including Kuwait (4,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%